Human values, civic participation, and wellbeing: analysis on their relationship among older Europeans - Vega-Tinoco, Andrea; Sánchez-García, Julia; Gil-Lacruz, Marta; Sierra Berdejo, María José; Gil-Lacruz, Ana Isabel (Frontiers in Psychology, 2024)
So far, both for the general and older population, research on human values and wellbeing mainly shows correlational associations but does not inquire about the direction of this relationship. This is also true for values and civic participation. Therefore, our objective is to identify the directional association between civic participation and Schwartz values, and between values and wellbeing, among older Europeans. For this purpose, a pseudo-panel was created from the cross-sectional data of the European Social Survey (ESS 2002(ESS -2018)), controlling for gender, age-group, country and level of studies (n=3926). The data analysis was performed using a cross-lagged model, applying both random-effects and fixed-effects models. Results show that, on the one hand, the relationship between participation and values is bidirectional, but the effect of civic participation on values is more significant since participating stimulates the development of certain values. On the other hand, although the relationship between values and wellbeing is also bidirectional, the effect of wellbeing on values is stronger since a given level of wellbeing favors the development of particular values. Thus, we conclude that civic participation should be promoted within the older population since it directly increases wellbeing, and moreover reinforces those (Growth-oriented) values that positively influence the health, happiness and life satisfaction of older people.